Mercados musicais-dançantes e periferias: trajetórias individuais e de circuitos de diversão em Salvador e Maceió - Fernando de Jesus Rodrigues (Universidade do Vale do Rio dos Sinos (UNISINOS), 2017)
From the trajectories of two characters – one from a musical scene – in Salvador and another from Maceió, I explore the course of differentiating their positions and, thus, I design aspects of the expansion of musical entertainment circuits in the “peripheries” of these cities. I highlight two problems: (i) the interpenetrations between repertoires of symbols and the functional differentiation of religious and diversion markets; and (ii) the relation between cultural agents and enterprises marked by power logics typical of illicit and highly criminalized markets in the space construction of symbolic struggles in the “peripheries”.